KARAKTERISTIK GEOLOGI TEKNIK DESA KATEKAN, KECAMATAN GANTIWARNO, KABUPATEN KLATEN, PROVINSI JAWA TENGAH - Wisnu Aji Dwi Kristanto; Fandika Agustiyar; Ayu Damayanti; Vanya Cesaria Evelina Sari (KURVATEK, 2021)
Supporting data for sustainable development is increasingly being considered to fulfill good primary development data. One of the data that is often ignored is the engineering geology of the land. These data are needed to describe the response of the land to various aspects imposed on the land from a geological and engineering point of view. Thus, it is necessary to investigate the characteristics of engineering geology before the land is used or as part of the evaluation. Katekan village, with its rapid population growth, requires the construction of various life support facilities. This is evidenced by the construction of many new houses in various village areas and access roads with cast and asphalt materials. The development that occurs, not a few uses agricultural land which has clay-rich soil material. Many problems occur in the construction, including house cracks, cracks in the road, and puddles. It becomes interesting to investigate related to geological engineering conditions. Investigation of the technical geological characteristics of Katekan Village, which was carried out by qualitative and quantitative field mapping, resulted in the distribution of rock units in the form of alluvial deposits of clay, sand, and silt. Slope variation between 3°-8°. The level of ease of excavation of rock mass ranges from easy to excavate to challenging to excavate. Rock bearing capacity is 72.42-154.63 t/m2, and the soil bearing capacity is 13.63-41.51 t/m2.